MOTIF PERSAHABATAN DAN KESEPIAN PADA SANTRI - Sulfianti Syamsul; Widyastuti widyastuti; Nur Hidayat Nurdin (Jurnal Psikologi TALENTA, 2018)
There are many factors that could make a person become lonely, one of the factors is the condition where the person have to live far from their parents and family, which is shown on the teenegers that lived in boarding school. Building a good friendship could help a person who feels loneliness. This research aims to determine the correlation of friendship motive towards loneliness on boarding school students, differences in the level of friendship motive on man students and women students, and the difference in levels of loneliness on man students and woman students. This research has 247 student subjects consisted of 172 man students and 75 woman students at the boarding school Darud Da'wah wal Irsyad Rahman Ambo Dalle Mangkoso. This research uses product moment person test and independent sample t-test. The results of this research show that was correlation of friendship motive towards loneliness (p = 0.000). Correlation coefficient of friendship motive toward loneliness of -0.618. There was no differences in the level of friendship motive men students and women students (p = 0.731). There was no difference in the level of loneliness men students and women students  (p = 0.150). The benefits of this research is to give an idea of the friendship motive and loneliness, especially the students at the boarding school.